THE GENETICS OF HUMAN MIGRATION. TRACING MIGRATIONS THROUGH THE GENOME - David Comas (Mètode Science Studies Journal, 2015)
Various academic disciplines shed light on human migrations, helping us to reconstruct the past. Studying the genetic diversity of human populations today reveals past demographic and migratory events that have left an imprint on our genome. Armed with knowledge of migrations in prehistoric times, we can test hypotheses put forward in other scientifi c disciplines. Similarly, the distribution of genetic diversity in the future will largely depend on today’s extensive human migrations, facilitated by technological advances.